Memelihara Citra Positif RI melalui Radio Taiwan Internasional - Yunus, Ulani (Humaniora, 2014)
Research aims to answer on how to maintain a positive image of the government of Indonesia through Radio Taiwan International. Research used literature study method through data collection compiled based on the results of previous researches in journals and discussing communication, government and media, especially radio media, as well as data collection from seminars. Results of the study indicate that the Indonesian community residing in Taiwan requires intensive media to fill their minds, so that they remain proud to be Indonesian. Thus the image of the government of Indonesia remains positive. Recommendation of this research is the government of Indonesia has to use the local radio as a medium to keep a positive image.